THE EFFECTIVENESS OF AROMATHERAPY LAVENDER IN REDUCING EMESIS GRAVIDARUM IN FIRST TRIMESTER PREGNANT WOMEN - Setiyowati, Widyah; Gunarmi, Gunarmi; Dedi, Blacius (Jurnal Kebidanan, 2024)
The discomfort that often occurs in pregnant women, especially in the first trimester of pregnancy, is vomiting nausea (Emesis Gravidarum). If emesis gravidarum occurs continuously and is not treated properly, it will cause symptoms of severe vomiting nausea to hyperemysis gravidarum which has adverse effects on the health of the mother and fetus. Emesis gravidarum during pregnancy can be administered pharmacologically and non-pharmacologically. Non-pharmacological actions that can be done, namely mothers can be recommended to eat often in small portions, acupuncture, and aromatherapy. One of the aromatherapy used to treat vomiting nausea is lavender aroma therapy. This study aims to find out how lavender aromatherapy affects vomiting nausea in pregnant women in the I trimester. The sample in this study was 38 I trimester pregnant women with complaints of vomiting nausea who did not use pharmacological therapy. Data analysis using the Wilcoxon test obtained the results of the p-value = 0.000 (<0.05) it can be concluded that Ha is accepted, which means that there is an influence of lavender aromatherapy in reducing emesis gravidarum in pregnant women in the I trimester. Advice can be given to pregnant women can use lavender aromatherapy as an alternative medicine to reduce emesis gravidarum. Keywords : Aromatherapy, Lavender, Nausea And Vomiting